A Philippine history of Denmark from pioneer settlers to permanently temporary workers - Andersen, Nina Trige (Philippine studies : historical and ethnographic viewpoints, 2017)
"In 1973 forty-nine women left the Philippines to work as chambermaids at the Hotel Scandinavia in Copenhagen. They became known as "The 49ers" and were among the last "Filipino Pioneers," as the arrivals of 1960-1973 referred to themselves. In late 1973 Denmark formally stopped issuing work permits for third-country nationals, which profoundly changed the conditions for later arrivals. Since the 2000s a new wave of migrants from the Philippines has entered Denmark on a much larger scale but under more precarious conditions. This article traces the lives of The 49ers and examines the relations between the generation of the Pioneers and the later migrants, illustrating a history of creating labor in motion."